Quality evaluation of waffles produced from the partial replacement of wheat flour with green banana flour and potato starch - Tran Ngoc Giau; Nguyen Minh Thuy; Vo Quoc Tien; Ngo Van Tai (My University, 2023)
1Institute of Food and Biotechnology, Can Tho University, Vietnam 2King Mongkut’s Institute of Technology Ladkrabang, Schoolof Food Industry, Bangkok, Thailand
Keywords: Potato starch; Food and Agricultural Sciences